Pengembangan Media Pembelajaran Gerakan Front Handspring Berbasis Android untuk Mahasiswa Olahraga S1 UNNES - Didik Iman Hartadi; Bambang Priyono; Tommy Soenyoto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to: 1) Develop an Android-based learning media for the front handspring movement tailored for undergraduate physical education students at Universitas Negeri Semarang (UNNES), 2) Assess the feasibility of the developed learning media, 3) Evaluate its effectiveness in enhancing students’ handspring skills. The research employed a Research and Development (R&D) design, validated by six experts. Trials were conducted with UNNES physical education students (small-scale: 6 students; large-scale: 40 students; practicality and effectiveness tests: 49 students). Data were collected using questionnaires and handspring skill tests. Data analysis involved Aiken’s V for validity, Cronbach’s Alpha for reliability, and descriptive quantitative analysis for effectiveness.The results indicated that the developed media is both valid and reliable, with expert validation scores of 0.95 (media) and 0.93 (content). Reliability testing yielded Alpha scores of 0.892 and 0.901, respectively. Effectiveness testing showed a significant improvement in handspring performance from an average pre-test score of 75 to a post-test score of 81, with a significance value of 0.000 < 0.005. Therefore, the Android-based learning media is considered effective in improving front handspring skills among physical education students at UNNES.